2014
DOI: 10.2147/ijn.s60346
|View full text |Cite
|
Sign up to set email alerts
|

Understanding improved osteoblast behavior on select nanoporous anodic alumina

Abstract: The aim of this study was to prepare different sized porous anodic alumina (PAA) and examine preosteoblast (MC3T3-E1) attachment and proliferation on such nanoporous surfaces. In this study, PAA with tunable pore sizes (25 nm, 50 nm, and 75 nm) were fabricated by a two-step anodizing procedure in oxalic acid. The surface morphology and elemental composition of PAA were characterized by field emission scanning electron microscopy and X-ray photoelectron spectroscopy analysis. The nanopore arrays on all of the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…In recent years, it has been recognized that biomaterial porosity greatly influences cellular behavior not only at the proliferative but also the differentiation stage (Bignon et al, 2003 ; Karageorgiou and Kaplan, 2005 ; Lew et al, 2012 ). Therefore, it has been suggested that by adapting surface properties to the desired cell behavior, we may open up the possibility of controlling cell behavior, thereby improving implant performance (Ni et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, it has been recognized that biomaterial porosity greatly influences cellular behavior not only at the proliferative but also the differentiation stage (Bignon et al, 2003 ; Karageorgiou and Kaplan, 2005 ; Lew et al, 2012 ). Therefore, it has been suggested that by adapting surface properties to the desired cell behavior, we may open up the possibility of controlling cell behavior, thereby improving implant performance (Ni et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…4 5 AAO can form different types of anodic oxides: a non-porous barrier type, when fabricated using neutral electrolytes, and a porous-type oxide, when fabricated using acidic electrolytes. Nanoporous alumina is a suitable template for the production of nanostructures 6 and has been used in medical applications, e.g., tissue engineering, in recent years based on reports that various types of cells, such as neurons, 7 hepatic cells, 8 smooth muscle cells, 9 keratinocytes, 10 fibroblasts, 11 and osteoblasts, 12 are capable of attaching to its surface. Furthermore, neurite outgrowth is known to be accelerated by pitch-dependent AAO substrates, 7 and hepatic cell growth is accelerated on self-supporting, mechanically stabilized nanoporous aluminum oxide membranes.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that enhancing the osteoblast density on the aluminum surface can be achieved by improving the surface roughness only and without any change in chemistry. [68] To study the importance of pore depth, Thakur et al studied the living cells (vascular endothelial cells (ECV 304) response on PAA surface. The cells were cultured on the nanoporous surface and after 1 day treated with polymerized actin in the presence of 3.7% formaldehyde.…”
Section: Cell Attachment On Naa Surfacesmentioning
confidence: 99%